2010
DOI: 10.1159/000321344
|View full text |Cite|
|
Sign up to set email alerts
|

Renal Replacement Therapy for Prevention of Contrast-Induced Acute Kidney Injury: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background: Contrast-induced acute kidney injury (CI-AKI) is an important cause of acute renal injury. Several clinical trials using renal replacement therapy (RRT) for prevention of CI-AKI yielded conflicting results. We performed a meta-analysis to assess the efficacy of prophylactic RRT on CI-AKI. Methods: Randomized controlled trials on CI-AKI using RRT were identified without language restriction in Cochrane library, Pubmed and Embase. Data extracted from literature were analyzed with Review manager and S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…It has been reported that 60-90 % of the contrast medium is removed during 1 session of hemodialysis. Clinical studies have been conducted on the basis of these findings to investigate the efficacy of hemodialysis, hemodiafiltration, and hemofiltration in the prevention of CIN [160][161][162][163][164][165][166][167][168][169]. However, most studies could not demonstrate the efficacy of these procedures in the prevention of CIN.…”
Section: Level Of Evidence: II Grade Of Recommendation: C2 Rationale mentioning
confidence: 99%
“…It has been reported that 60-90 % of the contrast medium is removed during 1 session of hemodialysis. Clinical studies have been conducted on the basis of these findings to investigate the efficacy of hemodialysis, hemodiafiltration, and hemofiltration in the prevention of CIN [160][161][162][163][164][165][166][167][168][169]. However, most studies could not demonstrate the efficacy of these procedures in the prevention of CIN.…”
Section: Level Of Evidence: II Grade Of Recommendation: C2 Rationale mentioning
confidence: 99%
“…In an effort to reconcile the disparate clinical trial findings, systematic reviews and meta-analyses have been performed to analyze the collective results of relevant studies [80,81] . Cruz et al [80] conducted a meta-analysis of blood purification therapies for the prevention of RCIN.…”
Section: Hemofiltration and Hemodialysismentioning
confidence: 99%
“…In sensitivity analyses that included only those studies of hemodialysis, inter-trial heterogeneity was not statistically significant, yet there was a trend toward greater risk for RCIN with hemodialysis compared with standard preventive care [80] . In a recently published meta-analysis, Song et al [81] compared the different modes of RRT in assessing the efficacy of prophylactic RRT on RCIN in 751 patients. They found considerable heterogeneity across trials (P < 0.00001).…”
Section: Hemofiltration and Hemodialysismentioning
confidence: 99%
“…We read with interest the meta-analysis by Song et al [1] on renal replacement therapy (RRT) for the prevention of contrast-induced acute kidney injury (CI-AKI). In principle we agree that whatever benefit prophylactic RRT may offer, this is likely limited to a high-risk population with a high pretest probability of CI-AKI, including those with severe chronic kidney disease (CKD).…”
Section: To the Editormentioning
confidence: 99%
“…Furthermore, in figure 3 of Song et al [1] , they indicate the number of patients who develop CI-AKI for each study.…”
mentioning
confidence: 99%